Northern Bobwhite Response to Vegetation Management and Recovery in South Texas - Rachel A. Smith; Leonard A. Brennan; Humberto L. Perotto-Baldivieso; Fidel Hernández (National Quail Symposium Proceedings, 2022)
The northern bobwhite (Colinus virginianus; hereafter, bobwhite) requires habitat structure and composition with grass cover for nesting, predator avoidance, and thermal refuge and forb cover for feeding on phytophagous arthropods and seeds. During the past 2 decades, many land managers with interest in promoting quail hunting opportunities have reduced or completely eliminated livestock across South Texas, USA, rangelands. Resting the land from grazing allows vegetation—especially grasses and forbs—to recover and thus provide nesting and foraging habitat for bobwhite and other birds. How bobwhite respond to postgrazing vegetation recovery is of keen interest to rangeland quail managers, but this topic is poorly known because case histories with quantitative data are lacking. Our objective was to investigate how bobwhite respond to the vegetation changes following removal of cattle grazing. Our study was conducted on a private ranch in Jim Hogg County, Texas and involved 3 different categories of postgrazing recovery and management: 1 area at 15 years post-cattle grazing where the landscape has been brush-sculpted and is actively managed since removal of cattle, 1 area at 3 years post-grazing with a previous stocking density of 7 ha/animal unit (high stocking density), and 1 area at 3 years post-grazing with a previous stocking density of 14 ha/animal unit (moderate stocking density). We trapped, radio-marked, and located bobwhites from March to September during 2015–2016 on the 3 comparative units. We estimated nest survival, adult breeding-season survival, home range size, and early winter density. We hypothesized that the 15-year postgrazing site would have higher early winter density, higher adult breeding season survival, and higher nest survival along with smaller mean home range size compared to the 2 more recently grazed sites. On average, the probability of a nest surviving the 23-day incubation period was highest on the 15-year postgrazing site at 0.61 ± 0.12 (mean nest survival ± standard error), with estimates of 0.32 ± 0.12 on the 3-year moderate postgrazing site and 0.33 ± 0.12 on the 3-year high postgrazing site. Adult breeding season survival did not differ among the 3 sites, and was instead influenced mostly by month within the season, probably a result of summer heat. An adult bobwhite had a 0.48 ± 0.04 probability of surviving the breeding season. Early winter density, after summer and fall production was complete, increased on all sites from 2015 to 2016 and was consistently highest on the 15-year postgrazing site. Home range sizes on the 15-year and 3-year moderate postgrazing sites were significantly larger than on the 3-year high postgrazing site. Additionally, landscape features around nest sites suggest lingering differences among the sites, supporting higher nest survival on the 15-year postgrazing site. These findings suggest that in South Texas, bobwhite populations can attain densities of approximately 2.0–2.9 birds/ha within 5 years after removal or reduction of cattle, given adequate rainfall.
Keywords: northern bobwhite; (Colinus virginianus); density; grazing; home range; survival